THE IMPACT OF REWARD AND RECOGNITION ON EMPLOYEE ENGAGEMENT AT PT. BANK SULUTGO, MANADO - Mesepy, Sharon Suri (Sam Ratulangi University, 2016)
ABSTRAK Â This study was conducted to examine the impact ofthe salary and respect for employee involvement. This research was specifically conducted in PT. BANK SULUTGO, Manado. The method used in this research is quantitative descriptive exploratory. The population in this study consisted of employees of PT. BANK SULUTGO. The results show the rewards and recognition can motivate the employee so they will work and provide more better performance so that it can provide more profits for the company. Keywords: Reward, Recognition, Employee Engagement, System. Â